Perceptions of Graduates from Online Accelerated Pre-licensure Second-degree Bachelor of Science in Nursing Programs on Quality of Educational Experience and Readiness for Clinical Practice. - Jones, Virginia L (Perceptions of Graduates From Online Accelerated Pre-Licensure Second-Degree Bachelor of Science in Nursing Programs on Quality of Educational Experience & Readiness for Clinical Practice, 2015)
There is an increasing use of distance learning methods being utilized for nursing education. Accelerated second-degree Bachelor of Science in nursing (ASDBSN) programs have increased rapidly from 31 in 1990 to 230 in 2013 with 33 more programs in the planning stages according to the American Association of Colleges of Nursing (2013). There are currently three identified online pre-licensure, ASDBSN programs. There are research studies focusing on graduates from this type of nursing programs using the traditional format, which is the face-to-face college experience, but a lack of literature regarding graduates of the online learning format.This qualitative descriptive study explored recent graduates' perceptions from two online ASDBSN programs related to quality of their educational experience and their preparation for clinical practice. Individual interviews were conducted with eleven recent graduates, all practicing registered nurses, in an online HIPPA protected video/audio conference room. This study's findings indicated that all participants felt they received a quality education. In addition, the participants felt they graduated from quality programs. The study also found that recent graduates of online ASDBSN programs expressed confidence and verbalized being well prepared for clinical practice, which is different from what is reported in the literature for typical graduates of traditional programs.